2002
DOI: 10.1021/es010146d
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Atrazine's Bound (Nonextractable) Residues Using Fractionation Techniques for Soil Organic Matter

Abstract: Atrazine's bound residues (BR), in the range of 10-40% of the applied atrazine,were obtained by laboratory incubation (56 d) of four soils having different capacities to degrade atrazine in relation to the presence or absence of a microflora able to mineralize the triazinic ring. Soil size fractionation followed by alkaline extraction, before and after HF treatment, and then acid hydrolysis with 2 M HCl in reflux conditions was applied to the soils containing BR. Most of the BR were in the finest fraction (<20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 37 publications
1
39
0
2
Order By: Relevance
“…The reason for atrazine in ground water is due to direct leaching, surface run-off or intrusion via particle binding. A continuous desorption and resulting mobility of atrazine in soils is also under discussion, with focus on the formation of "bound residues" (9 ). Degradation and metabolism of atrazine in soil occurs through microbial activity and non-biotic processes, such as hydrolysis, photo-degradation and oxidation, leading simultaneously to the formation of bound residues (10 ).…”
Section: The S-triazine Herbicide Atrazine [2-chloro-4-(ethylamino)-6mentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for atrazine in ground water is due to direct leaching, surface run-off or intrusion via particle binding. A continuous desorption and resulting mobility of atrazine in soils is also under discussion, with focus on the formation of "bound residues" (9 ). Degradation and metabolism of atrazine in soil occurs through microbial activity and non-biotic processes, such as hydrolysis, photo-degradation and oxidation, leading simultaneously to the formation of bound residues (10 ).…”
Section: The S-triazine Herbicide Atrazine [2-chloro-4-(ethylamino)-6mentioning
confidence: 99%
“…Numerous investigations have stated that the distribution of atrazine residues in soil is mainly dependent on the soil organic carbon (e.g. humin, humic and fulvic acids) (15 ) and the clay content (16 ), with the majority of the atrazine residues are located in soil particle fractions <20µm (9 ).…”
Section: The S-triazine Herbicide Atrazine [2-chloro-4-(ethylamino)-6mentioning
confidence: 99%
“…Because of the large use of atrazine (AT) to control annual grasses and broad-leaved weeds in several crops, in roadside verges and golf courses, intense research has been performed to investigate its environmental impacts. [2][3][4][5][6] Several authors have reported the presence of AT and its metabolites in surface and ground waters, as well as other s-triazines such as simazine, ametryne and propazine. 7 Although the presence of AT metabolites is indicative of herbicide degradation, some of them, especially deethylatrazine (DEA) and deisopropylatrazine (DIA), have similar toxicity, greater water solubility and weaker interaction with soil components than the parent herbicide.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using degradative techniques such as pyrolysis and chemical hydrolysis, and pesticides labelled with 13 C or 15 N, Guthrie et al (1999), Loiseau et al (2000), Loiseau and Barriuso (2002), and Dignac et al (2003) showed a partial release of bound residues. Their results showed that a major part of bound residues were compounds of chemical structure similar to that of the parent compound.…”
Section: Introductionmentioning
confidence: 99%